Development of a proficiency‐based virtual reality simulation training curriculum for laparoscopic appendicectomy - Sirimanna, Pramudith; Gladman, Marc A. (ANZ journal of surgery, 2017)
Background Proficiency‐based virtual reality (VR) training curricula improve intraoperative performance, but have not been developed for laparoscopic appendicectomy (LA). This study aimed to develop an evidence‐based training curriculum for LA. Methods A total of 10 experienced (>50 LAs), eight intermediate (10–30 LAs) and 20 inexperienced (<10 LAs) operators performed guided and unguided LA tasks on a high‐fidelity VR simulator using internationally relevant techniques. The ability to differentiate levels of experience (construct validity) was measured using simulator‐derived metrics. Learning curves were analysed. Proficiency benchmarks were defined by the performance of the experienced group. Intermediate and experienced participants completed a questionnaire to evaluate the realism (face validity) and relevance (content validity). Results Of 18 surgeons, 16 (89%) considered the VR model to be visually realistic and 17 (95%) believed that it was representative of actual practice. All ‘guided’ modules demonstrated construct validity (P < 0.05), with learning curves that plateaued between sessions 6 and 9 (P < 0.01). When comparing inexperienced to intermediates to experienced, the ‘unguided’ LA module demonstrated construct validity for economy of motion (5.00 versus 7.17 versus 7.84, respectively; P < 0.01) and task time (864.5 s versus 477.2 s versus 352.1 s, respectively, P < 0.01). Construct validity was also confirmed for number of movements, path length and idle time. Validated modules were used for curriculum construction, with proficiency benchmarks used as performance goals. Conclusion A VR LA model was realistic and representative of actual practice and was validated as a training and assessment tool. Consequently, the first evidence‐based internationally applicable training curriculum for LA was constructed, which facilitates skill acquisition to proficiency.